PENGARUH TINDAKAN SUCTION PADA PERUBAHAN SATURASI OKSIGEN PADA PASIEN PNEUMONIA - Yogasara, Yoseph; Rakhmawati, Arifah; Murtiani, Farida; Widiantari, Aninda Dinar (Program Studi S1/DIII-Keperawatan Universitas Imelda Medan, 2023)
ICU patients who use mechanical ventilators need intensive monitoring including blood gas analysis which contains oxygen saturation (SpO2). Suctioning is performed to clear airway, reduce sputum retention and prevent lung infection in advance. We studied effect of suctioning on oxygen saturation in pneumonia patients who used mechanical ventilator. This research was a quasi-experimental research with one group pretest-posttest design. We investigated 30 intensive care unit patients. Intervention was suctioning in semifowler position. Oxygen saturation was measured with pulse oximetry. Results showed that average oxygen saturation before intervention was 94,87% while after intervention was 96,93%. We performed Wilcoxon test and obtained p-value = 0.001. It concluded that suction affects oxygen saturation in pneumonia patients on ventilators in the ICU RSPI Sulianti Saroso with an average increase of 2.067%.